2006
DOI: 10.1111/j.1365-2249.2006.03013.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of nontransgenic mesenteric lymph node cells induces colitis in athymic HLA-B27 transgenic nude rats

Abstract: SummaryHLA-B27 transgenic (TG) rats develop spontaneous colitis when colonized with intestinal bacteria, whereas athymic nude (rnu/rnu) HLA-B27 TG rats remain disease free. The present study was designed to determine whether or not HLA-B27 expression on T cells is required for development of colitis after transfer of mesenteric lymph node (MLN) cells into rnu/rnu HLA-B27 recipients. Athymic nontransgenic (non-TG) and HLA-B27 TG recipients received MLN cells from either TG or non-TG rnu /+ + + + heterozygous do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…16 Although the exact underlying mechanism has not been characterized yet, it has been shown that HLA-B27-expressing innate immune cells have an essential role in determining mucosal immune responses to commensal bacteria in the development of colitis in transgenic rats. 17 Additionally, we have shown in several controlled rat and human studies that dietary calcium improves intestinal resistance against infections with foodborne bacterial pathogens and that it strengthens the mucosal barrier. [18][19][20] It is hypothesized that calcium exerts this protection in part by precipitating irritating bile acids and fatty acids, thereby reducing cytotoxicity of the fecal stream.…”
mentioning
confidence: 98%
“…16 Although the exact underlying mechanism has not been characterized yet, it has been shown that HLA-B27-expressing innate immune cells have an essential role in determining mucosal immune responses to commensal bacteria in the development of colitis in transgenic rats. 17 Additionally, we have shown in several controlled rat and human studies that dietary calcium improves intestinal resistance against infections with foodborne bacterial pathogens and that it strengthens the mucosal barrier. [18][19][20] It is hypothesized that calcium exerts this protection in part by precipitating irritating bile acids and fatty acids, thereby reducing cytotoxicity of the fecal stream.…”
mentioning
confidence: 98%
“…Even if rnu/rnu TG rats carry the disease-prone B27 transgenic locus, they are protected from disease, whereas the presence of T cells in their heterozygous rnu/ϩ TG littermates coincides with the development of colitis under SPF conditions. 12,13 The critical role of T cells in the induction of intestinal inflammation in this model was further emphasized by the development of colitis in SPF rnu/rnu HLA-B27 TG recipients after T cells had been transplanted, with CD4 ϩ T cells being more efficient than CD8 ϩ T cells in transferring disease. 12 Most studies of HLA-B27 TG rats have been carried out under SPF conditions.…”
mentioning
confidence: 98%
“…23 In contrast, non-TG nude recipients remain disease-free even after transfer of activated TG T cells. 23 Breban et al 24 previously reported that transfer of bone marrow-cells from colitic HLA-B27 TG rats to lethally irradiated disease-resistant non-TG rats or rats with low expression levels of HLA-B27 induced intestinal inflammation, and the disease was related to the generation of donor-derived CD11b/c-expressing cells. Conversely, established disease in TG recipients was reversed 6 -8 weeks after transfer of non-TG bone marrow cells.…”
mentioning
confidence: 94%
“…20,21 It has been demonstrated that development of intestinal inflammation in HLA-B27 TG rats is dependent on HLA-B27 expression by cell types, most likely dendritic cells and macrophages, that function as accessory cells for T cell immune responses. Colitis does not occur in nude HLA-B27 TG rats but rapidly develops after T cell reconstitution, 22,23 whether or not the transferred T cells express HLA-B27. 23 In contrast, non-TG nude recipients remain disease-free even after transfer of activated TG T cells.…”
mentioning
confidence: 97%
See 1 more Smart Citation